Evidence-based identification of the most important livestock related zoonotic diseases in Kampala, Uganda - Makita, K.; Fèvre, Eric M.; Waiswa, C.; Kaboyo, W.; Eisler, M.C.; Welburn, S.C. (Japanese Society of Veterinary Science, 2011)
Urban and peri-urban livestock farming in developing countries plays an important role in food security in cities; however it brings with it zoonotic risks. The present study was conducted to identify the most important livestock farming-related zoonotic diseases among the human population in urban and peri-urban areas of Kampala, Uganda and to assess the risks from such farming. A framework for identifying livestock farming-related significant zoonoses was developed. The process consisted of screening of medical record summaries for zoonotic diagnoses, selection of the zoonoses which are related to livestock farming, case estimation of the identified zoonoses and evidence-based reassurance of the importance of diseases. Medical records in the Mulago National Referral Hospital were used for the analysis. Leaders and residents of 75 Local Councils (LC1s: villages; 48 urban, 11 peri-urban and 16 rural) randomly selected in Kampala were interviewed for information regarding livestock farming systems, value chains and use of medical service units. Twelve zoonoses were identified in the screening and four out of them were related to livestock farming: animal sourced food-borne gastroenteritis, brucellosis, Taenia solium neuro-cysticercosis and Mycobacterium bovis tuberculosis. Livestock farming, value chain and severity of the diseases confirmed that all four diseases were important. Poor geographical correlation between animals in peri-urban and rural areas and patients in urban areas suggested that the majority of these zoonoses were caused by informally-marketed foods.